Buddhism and postmodern imaginings in Thailand : the religiosity of urban space - Taylor, James (Aldershot : Ashgate, 2008)
"This book presents a rethink on the significance of Thai Buddhism in an increasingly complex and changing post-modern urban context, especially following the financial crisis of 1997. Defining the cultural nature of Thai 'urbanity', the implications for local/global flows, interactions and emergent social formations, James Taylor opens up new possibilities in understanding the specificities of everyday urban life as this relates to perceptions, conceptions and lived experiences of religiosity."--BOOK JACKET.
Includes bibliographical references (p. [205]-229) and index.
Keywords: Buddhism -- Thailand; Sacred space -- Thailand; Thailand -- Religious life and customs